MISKONSEPSI TUKANG BANGUNAN DALAM TEKNIK MEMBANGUN KONSTRUKSI TAHAN GEMPA - Dalil Herman, Nanag (TERAS)
This article is taken from a small section of the dissertation research, about development of a model program to improve the competence of transmigrantion community through the pottential environment based training. This paper will only present a small description of the research, that is concerning misconceptions of the workers / builders as a research subject, the technical knowledge to build earthquake-resistant housing construction. Research done by a